2013
DOI: 10.1089/jpm.2012.0591
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Pattern of Response When Morphine Is Used To Treat Chronic Refractory Dyspnea

Abstract: Background: While evidence supports using sustained release morphine for chronic refractory breathlessness, little is known about the longitudinal pattern of breathlessness intensity as people achieve symptomatic benefit. The aim of this study is to describe this pattern.Methods: This secondary analysis used breathlessness intensity scores (100 mm visual analogue scale (VAS)) from a prospective, dose increment study of once daily (morning) sustained release morphine for chronic refractory breathlessness. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 33 publications
(23 reference statements)
2
30
0
Order By: Relevance
“…This evidence consists of a Cochrane meta-analysis,12 a systematic review,24 a randomized trial,10 and several studies 16,22. Sustained-release morphine should be considered as a first line treatment and should be initiated at a low dose regularly and titrated upward over days and weeks, balancing beneficial and adverse effects 25,26. All treatments assume adequate follow-up of the patient’s clinical condition and symptoms, including proper prophylaxis and treatment for expected effects such as opioid-related constipation 10,25.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence consists of a Cochrane meta-analysis,12 a systematic review,24 a randomized trial,10 and several studies 16,22. Sustained-release morphine should be considered as a first line treatment and should be initiated at a low dose regularly and titrated upward over days and weeks, balancing beneficial and adverse effects 25,26. All treatments assume adequate follow-up of the patient’s clinical condition and symptoms, including proper prophylaxis and treatment for expected effects such as opioid-related constipation 10,25.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that opioid-na€ ıve patients could be slowly titrated because inadequate dosing may generate no response. 23 In this study, 40% of patients with episodic breathlessness were receiving a pharmacological treatment for it, and about 80% of them were receiving oral opioids. Oral opioids do not fit the temporal characteristics of episodic breathlessness, as their effect starts about 30 minutes after administration.…”
Section: Treatment Of Breathlessness and Episodic Breathlessnessmentioning
confidence: 73%
“…Chronic refractory breathlessness [7][8][9] Chronic breathlessness that is refractory to treatments for the underlying condition Episodic breathlessness [10][11][12][13][14] Severe worsening of breathlessness intensity or unpleasantness beyond usual fluctuations [13][14][15] Breathlessness can be very frightening for patients and families 25,26,28-31 and can have a devastating impact on their lives, severely limiting well-being and quality of life (QoL). 2,[32][33][34] It is associated with considerable anxiety, depression, fear, social isolation, deconditioning and disability, 21,28,29,31,35,36 and shortened life expectancy.…”
Section: Term Definitionmentioning
confidence: 99%
“…Complete a needs assessment around breathlessness, map it to current service provision and consider areas for service improvement (P1) 8 (7)(8)(9) Prioritise supporting development of breathlessness-triggered services, which span all stages of multiple diseases and conditions (P2) 8 (7-9)…”
Section: Strong Agreement Low Consensusmentioning
confidence: 99%
See 1 more Smart Citation